Back Cover Image. (21st January 2019) - Feng, Xuning; Xu, Chengshan; He, Xiangming; Wang, Li; Gao, Shang; Ouyang, Minggao
Abstract : The back cover image is based on the Research Article A graphical model for evaluating the status of series‐connected lithium‐ion battery pack, by Xuning Feng et al., https://doi.org/10.1002/er.4305 .